2020
DOI: 10.3389/fphys.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biochemical Composition and Energy Reserves Associated With Sexual Maturation of Octopus maya

Abstract: Climate conditions are related to changes in the biochemical composition of several tissues and associated to the processes of growth and sexual development in cephalopods. The biochemical composition (protein, glucose, cholesterol, acylglycerides) and hemocytes of the hemolymph, the hepatosomatic and gonadosomatic indices, and the reserves of the gonad, hepatopancreas and muscle (lipids, glycogen, and caloric value of muscle) of Octopus maya were determined and related to sex and season. A total of 154 wild a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
6
1
Order By: Relevance
“…This model would be justified either by not having found trade-offs between tissues, that is, a transference of energy from tissue to tissue, or by having observed a positive correlation between somatic and reproductive condition during maturation. However, this is in contrast with the theory postulated by other authors consisting of the muscle (i.e., mantle) and digestive gland providing some energy for reproduction (i.e., capital breeding) (e.g., O'Dor and Wells, 1978;Seibel et al, 2000;Jackson et al, 2004;Lin et al, 2019;Pascual et al, 2020).…”
Section: Introductioncontrasting
confidence: 65%
See 3 more Smart Citations
“…This model would be justified either by not having found trade-offs between tissues, that is, a transference of energy from tissue to tissue, or by having observed a positive correlation between somatic and reproductive condition during maturation. However, this is in contrast with the theory postulated by other authors consisting of the muscle (i.e., mantle) and digestive gland providing some energy for reproduction (i.e., capital breeding) (e.g., O'Dor and Wells, 1978;Seibel et al, 2000;Jackson et al, 2004;Lin et al, 2019;Pascual et al, 2020).…”
Section: Introductioncontrasting
confidence: 65%
“…Regarding octopods, those particularities outlined previously are also common, for instance, the accumulation of lipids in the ovary ( Pollero and Iribarne, 1988 ; Rosa et al, 2004b ) and in the digestive gland in some cases ( Lourenço et al, 2014 ; Pascual et al, 2020 ). However, there are several other points of dissent such as the absence or not of any variation in the protein content in the digestive gland and the ovary ( Rosa et al, 2004a , b ), or the differences regarding the content of glycogen in any of these tissues ( Olivares et al, 2019 ; Pascual et al, 2020 ). Finally, during spawning and post-spawning stages it is frequently found a decrease in proteins and/or lipids both in the mantle and the digestive gland of different species of cephalopods either sampled in the wild ( Pollero and Iribarne, 1988 ; de Moreno et al, 1998 ; Zamora and Olivares, 2004 ; Kilada and Riad, 2008 ) or as observed from lab studies ( Castro et al, 1992 ; García-Garrido et al, 2010 ; Morillo-Velarde et al, 2013 ).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Bogevik et al [ 11 ] discovered that phospholipid and LC-PUFA metabolism changed dramatically in the liver and gonad during the sexual maturation of Salmo salar . Cristina et al [ 12 ] revealed changes in metabolites and energy reserves by analyzing biochemical indicators of gonad, liver and muscle during the sexual maturation of Octopus maya . These studies demonstrated that biochemical indicators and metabolic changes with the liver as the target organ could be used to explore the mobilization and repartition of nutrients and energy during the sexual maturation of fish.…”
Section: Introductionmentioning
confidence: 99%